Redox Regulation of Nrf2 in Cisplatin-Induced Kidney Injury - Kranti A. Mapuskar; Casey F. Pulliam; Diana Zepeda-Orozco; Benjamin R. Griffin; Muhammad Furqan; Douglas R. Spitz; Bryan G. Allen (MDPI AG, 2023)
Cisplatin, a potent chemotherapeutic agent, is marred by severe nephrotoxicity that is governed by mechanisms involving oxidative stress, inflammation, and apoptosis pathways. The transcription factor Nrf2, pivotal in cellular defense against oxidative stress and inflammation, is the master regulator of the antioxidant response, upregulating antioxidants and cytoprotective genes under oxidative stress. This review discusses the mechanisms underlying chemotherapy-induced kidney injury, focusing on the role of Nrf2 in cancer therapy and its redox regulation in cisplatin-induced kidney injury. We also explore Nrf2's signaling pathways, post-translational modifications, and its involvement in autophagy, as well as examine redox-based strategies for modulating Nrf2 in cisplatin-induced kidney injury while considering the limitations and potential off-target effects of Nrf2 modulation. Understanding the redox regulation of Nrf2 in cisplatin-induced kidney injury holds significant promise for developing novel therapeutic interventions. This knowledge could provide valuable insights into potential strategies for mitigating the nephrotoxicity associated with cisplatin, ultimately enhancing the safety and efficacy of cancer treatment.